Effects of Mexican peso depreciation on pork market - Almazan-Figueroa, Obdulia; Rebollar-Rebollar, Samuel; Velázquez-Villalva, Hector Hugo; Gómez-Tenorio, Germán; Hernández-Martínez, Juvencio (Agronomía Mesoamericana, 2018)
The exchange depreciation serves as a protection mechanism for domestic production and to reduce imports. The objective was to evaluate the effect of two scenarios of exchange rate depreciation on the production, consumption and imports of carcasses pork meat regionally in Mexico in 2015 and 2016. The country was divided into two importation points (internment point one, internment point two) and eight production and consumer regions: Northwest, North, Northeast, Midwest, Central-East, South, East, Yucatan Peninsula. A non-linear programming model was used. Under optimal conditions, the model underestimated domestic production by 0.4% and overestimated regional and national imports and consumption by 2.5% and 0.4%, respectively, with an optimal social net value (SNV) of 21.66 billions of dollars. In relation to the optimal model, a 15.1% and 20.9% exchange depreciation would imply increasing national production by 0.3% and 0.4%, reduce imports by 1,5% to 2%, reduce domestic consumption 0.5% and 0.6%, and decrease the SNV by 0.10 and 0.13%. Under the previously given conditions it is concluded that a regional level, the Mexican carcass pork market is sensitive to exchange depreciation, protects domestic producers while damages both importation and consumers.